Mairtin O Direain - O Direáin, Mairtin,O hAnluain, Eoghan,O HAnluain, Eoghan (Cló lar-Chonnacht, 2010)
(An Irish-language title) Inis Mor artist Sean O Flaithearta has teamed up with publishers Clo Iar-Chonnacht to produce a new collection of Mairtin O Direain's poetry to mark the centenary of the Aran poet's birth. Mairtin O Direain. Na Danta (edited by Eoghan O hAnluain) features the collected poems from the acknowledged master stylist of poetry in Irish in the twentieth century. This collection contains all of the poems from Mairtin O Direain: Danta 1939-1979 as well as some previously unpublished works..
Description based on publisher supplied metadata and other sources